Magnetic resonance imaging contrast-enhancement with superparamagnetic iron oxide nanoparticles amplifies macrophage foam cell apoptosis in human and murine atherosclerosis. Issue 17 (23rd March 2022) - Segers, Filip M E; Ruder, Adele V; Westra, Marijke M; Lammers, Twan; Dadfar, Seyed Mohammadali; Roemhild, Karolin; Lam, Tin Sing; Kooi, Marianne Eline; Cleutjens, Kitty B J M; Verheyen, Fons K; Schurink, Geert W H; Haenen, Guido R; et al.
Abstract: Aims: (Ultra) Small superparamagnetic iron oxide nanoparticles, (U)SPIO, are widely used as magnetic resonance imaging contrast media and assumed to be safe for clinical applications in cardiovascular disease. As safety tests largely relied on normolipidaemic models, not fully representative of the clinical setting, we investigated the impact of (U)SPIOs on disease-relevant endpoints in hyperlipidaemic models of atherosclerosis. Methods and results: RAW264.7 foam cells, exposed in vitro to ferumoxide (dextran-coated SPIO), ferumoxtran (dextran-coated USPIO), or ferumoxytol [carboxymethyl (CM) dextran-coated USPIO] (all 1 mg Fe/mL) showed increased apoptosis and reactive oxygen species accumulation for ferumoxide and ferumoxtran, whereas ferumoxytol was tolerated well. Pro-apoptotic (TUNEL + ) and pro-oxidant activity of ferumoxide (0.3 mg Fe/kg) and ferumoxtran (1 mg Fe/kg) were confirmed in plaque, spleen, and liver of hyperlipidaemic ApoE −/− ( n = 9/group) and LDLR −/− ( n = 9–16/group) mice that had received single IV injections compared with saline-treated controls. Again, ferumoxytol treatment (1 mg Fe/kg) failed to induce apoptosis or oxidative stress in these tissues. Concomitant antioxidant treatment (EUK-8/EUK-134) largely prevented these effects in vitro (−68%, P < 0.05) and in plaques from LDLR −/− mice (−60%, P < 0.001, n = 8/group). Repeated ferumoxtran injections of LDLR −/− mice with pre-existing atherosclerosis enhanced plaque inflammation and apoptosis but did not alter plaque size. Strikingly, carotid artery plaques of endarterectomy patients who received ferumoxtran (2.6 mg Fe/kg) before surgery ( n = 9) also showed five-fold increased apoptosis (18.2 vs. 3.7%, respectively; P = 0.004) compared with controls who did not receive ferumoxtran. Mechanistically, neither coating nor particle size seemed accountable for the observed cytotoxicity of ferumoxide and ferumoxtran. Conclusions: Ferumoxide and ferumoxtran, but not ferumoxytol, induced apoptosis of lipid-laden macrophages in human and murine atherosclerosis, potentially impacting disease progression in patients with advanced atherosclerosis.